Are patient expectations associated with treatment outcomes in individuals with chronic low back pain? A systematic review of randomised controlled trials - Walid Jumma Mohamed Mohamed (2020)
© 2020 The Authors. International Journal of Clinical Practice published by John Wiley & Sons Ltd Aim: The importance of patient expectations (PEs) on treatment outcomes is poorly understood in clinical practice. The aim of this review is to investigate the evidence behind association between pre-treatment PEs and treatment outcomes such as pain intensity (PI), level of function (LF) and health-related quality of life (HRQoL) among individuals with chronic low back pain (CLBP). Methods: A systematic search was conducted for randomised controlled trials published between 1946 and May 2019 across major databases using the key MeSH terminologies. The association between PEs and PI, LF and HRQoL were extracted and categorised into positive, negative or no association for analysing the data. A descriptive synthesis was conducted and the association between PEs and PI, LF and HRQoL were reported. Results: Among the total of seven trials, two trials demonstrated a positive association between PEs and PI in short (≤6 weeks) and long term (>6 months), while another two trials demonstrated no association at medium term (>6 weeks-≤6 months). About four trials demonstrated a positive significant association between PEs and LF, 2 at medium and 2 at long terms. The only available trial demonstrated no association between PEs and HRQoL at medium term. Conclusion: PEs is associated with PI at short and long terms. Also, evidence suggests association between PEs and LF at medium and long terms. Currently, there is no evidence of association between PEs and HRQoL. Further studies with valid tools to measure PE are warranted among individuals with CLBP.